The construction of environmental philosophy rooted in religiosity - Syefriyeni, Syefriyeni (HTS teologiese studies, 2023)
One of the causes of poor human-environment relations is the separation of the study of natural philosophy and human philosophy. The awareness to combine natural and human philosophy has been sparked by thinkers such as Henryk Skolimowski and Fritjof Capra. However, both are seen as not showing clear root values. Meanwhile, Sayyed Hossein Nasr has brought the concept of value in the combination of natural philosophy with human philosophy. However, he describes it as a mystical concept that is too complex for many people to understand. Buya Hamka, with his monumental work on Al-Azhar commentary, has succeeded in combining natural and human philosophy based on clear values. Hamka is a multidimensional thinker with thinking characteristics that grow and blend into socio-cultural and religious so that many groups see it as more populist and can understand it. Hamka’s thinking way can be an alternative frame of reference for environmental problems. The Hamka concept constructs three main pillars: transcendent consciousness, caliphate and qana’ah. Transcendent consciousness is human appreciation based on religiosity. Caliphate is the role of humans to become mushlih (nature sustainer), preservers and guardians in efforts to beautify nature, and qana’ah encourages humans to take advantage of nature without exploiting it.Contribution: This research’s main contribution is offering an alternative concept of environmental philosophy construction based on religiosity. This concept is seen as a very accessible paradigm in most people’s minds and is not complicated. This paradigm can be disseminated and applied to many people, including in the junior high school environment, as a form of concern for the natural environment and sustainable life.